SISTEM PENERIMAAN SISWA BARU BERBASIS WEB PADA PKBM (PUSAT KEGIATAN BELAJAR MASYARAKAT) ATHREE - Iin Seprina; Tina Albiah (JURNAL ILMIAH BETRIK, 2023)
PKBM Athree is one of the agencies operating in the education sector that requires appropriate data sources and data processing in order to create accurate data that can support the decision-making process properly and precisely. The information system for new student admissions at PKBM Athree, so far the system used is still manual, namely that prospective students in the registration process enter data by writing on the registration form after the data is written on the new student admission form, then it is recorded by the PSB committee into the computer, however The problem is that many prospective students, especially those from outside the city, find it difficult with the manual system and of course need an information system that makes registration easier. The research method used in this research is Xtreme Programming (XP), namely to design a web-based information system for new student admissions that can be accessed via a web browser. This new student admission information system was built using the PHP programming language and utilizes the MySQL database as the database server. The result of this research is a web-based new student admissions information system that has the ability to make it easy for prospective new students to obtain all information about new student admissions, and carry out the registration process online.